La literatura latinoamericana en versión francesa Trabajos del equipo MEDET LAT - Guerrero, Gustavo; Camenen, Gersende (Latin American Literatures in the World / Literaturas Latinoamericanas en el Mundo, 2021)
This volume is the first sistematic study of French editorial mediation in the internationalization process of Latin-American literatures. It opens a new field of investigation - Latin-American literary works translated into French - and develops methodological tools to extend this type of study to other literatures from the Global South.